Materials in Organic Electrochemical Transistors for Bioelectronic Applications: Past, Present, and Future. (13th December 2018) - Moser, Maximilian; Ponder, James F.; Wadsworth, Andrew; Giovannitti, Alexander; McCulloch, Iain
Abstract: Organic electrochemical transistors are bioelectronic devices that exploit the coupled nature of ionic and electronic fluxes to achieve superior transducing abilities compared to conventional organic field effect transistors. In particular, the operation of organic electrochemical transistors relies on a channel material capable of conducting both ionic and electronic charge carriers to ensure bulk electrochemical doping. This review explores the various types of organic semiconductors that are employed as channel materials, with a particular focus on the past 5 years, during which the transducing abilities of organic electrochemical transistors have witnessed an almost tenfold increase. Specifically, the structure–property relationships of the various channel materials employed are investigated, highlighting how device performance can be related to functionality at the molecular level. Finally, an outlook on the field is provided, in particular toward the design guidelines of future materials and the challenges ahead in the field. Abstract : Organic electrochemical transistors are attracting significant attention due to their excellent ability to transduce ionic into electrical fluxes, thus rendering them ideal devices for communication across the abiotic–biotic interface. This review covers the research progress on the various organic semiconductors employed as the channel materials, providing insights into structure–property relationships of current materials and design guidelines for future ones.